Adrià Targa (1987). «Acròpolis» (fragment) - Targa, Adrià (ΑΕΡΗΔΕΣ / TORRE DELS VENTS, 2024)
Adrià Targa. 2024. Acròpolis [Premi Jocs Florals de Barcelona 2024]. Col·lecció Cadup. Barcelona: Godall Edicions.